2020
DOI: 10.32394/rpzh.2020.0100
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of occurrence of metabolic syndrome risk factors in children and adolescents from the city of Wrocław and surroundings

Abstract: Background. A recently growing number of children and adolescents with overweight or obesity is indicative of the need for diagnosing their complications that may appear in the early childhood. For this reason, diagnostic criteria were developed for components of the metabolic syndrome (MS) also for these groups of the population. Objective. This study was aimed at evaluating the frequency of metabolic syndrome risk factors occurrence in children and adolescents from the city of Wrocław and surroundings depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…According to the International Diabetes Federation (IDF) criteria, among children aged 10–16 years, MetS is diagnosed if there is central obesity (≥90 centile) and two of the following factors: fasting glucose ≥ 100 mg/dL or previously diagnosed type 2 diabetes mellitus, SBP ≥ 130 mmHg or DBP ≥ 85 mmHg, serum TG ≥ 150 mg/dL and high-density lipoprotein cholesterol (HDLc) < 40 mg/dL. Piotrowska et al [ 28 ] showed that at least one component of MetS was found in approximately 15.0% of 771 students aged 10–18 years. In the study group, the most common MetS components were excessive WC, reduced HDLc, elevated serum TG and elevated BP.…”
Section: Criteria For the Diagnosis Of Metsmentioning
confidence: 99%
“…According to the International Diabetes Federation (IDF) criteria, among children aged 10–16 years, MetS is diagnosed if there is central obesity (≥90 centile) and two of the following factors: fasting glucose ≥ 100 mg/dL or previously diagnosed type 2 diabetes mellitus, SBP ≥ 130 mmHg or DBP ≥ 85 mmHg, serum TG ≥ 150 mg/dL and high-density lipoprotein cholesterol (HDLc) < 40 mg/dL. Piotrowska et al [ 28 ] showed that at least one component of MetS was found in approximately 15.0% of 771 students aged 10–18 years. In the study group, the most common MetS components were excessive WC, reduced HDLc, elevated serum TG and elevated BP.…”
Section: Criteria For the Diagnosis Of Metsmentioning
confidence: 99%